Perspektif Fiqh Muamalah Terhadap Kepemilikan Dan Jual Beli Hasil Penambangan Emas Ilegal Di Sungai Batang Masumai Kabupaten Merangin - Putra, Rama Satria; Karima, Azzahra (Al-Bayyinah, 2025)
Illegal gold mining practices in the Batang Masumai River area of Merangin Regency have been ongoing for years and have become the main livelihood for some residents. This activity is carried out without official government permits and by residents living along the riverbanks, thus falling into the category of illegal mining. This study aims to analyze the ownership and trade of gold resulting from this mining from the perspective of fiqh muamalah. The method of this study is field research (qualitative) using a normative-empirical approach, with data collection techniques through observation and interviews with miners as well as gold traders. The data is analyzed through stages of collection, reduction, presentation, and conclusion. The findings of this study indicate that gold obtained from illegal mining does not fulfill the conditions and requirements to be legally traded because it is sourced from activities that violate the law, damage the environment, and have the potential to unilaterally infringe on public property rights. The buying and selling of gold from illegal mining cannot be justified from the perspective of fiqh muamalah, as it does not meet the elements of lawful ownership and public benefit.